Evaluation of hybrid learning in college using CIPP model - Aman, Aman; Setiawan, Risky; Prasojo, Lantip Diat; Mehta, Kunal (Jurnal Penelitian dan Evaluasi Pendidikan, 2021)
Learning in the millennial era provides significant changes in technology and communication. The COVID pandemic period requires every educational institution, especially universities, to carry out online learning. This influences the performance of lecturers in the online learning process, especially the implementation of hybrid learning at Universitas Negeri Yogyakarta (UNY). The purpose of this study is to (1) describe the implementation of hybrid learning at UNY; (2) know the hybrid learning lecture model carried out at UNY; (3) describe the results of hybrid learning evaluation. This research is an evaluation study with a mixed-method approach that is a mixture of qualitative and quantitative. The evaluation model selected is the CIPP model from Stufflebeam. This model was chosen because the evaluation is comprehensive, including (1) context, (2) input, (3) process, and (4) product. The results show that the hybrid learning evaluation model developed through the instrument already met an excellent construct of loading factor values and had a composite reliability score above 0.7 and Cronbach alpha above 0.6. Implementation of difficulties or obstacles to hybrid learning includes heterogeneity of origin of student residence to make the emergence of internet network signal problems. In comparison, the problem of lecturers is that not all lecturers have skills for technology and media in the implementation of hybrid learning. The results of hybrid learning evaluation showed that the value of context, input, process, and product aspects fall into the category of "excellent," i.e., with a total average score of 3.05.